2016
DOI: 10.2147/cia.s110718
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the effects of star fruit consumption on antioxidant and lipid status in elderly Thai individuals

Abstract: ObjectiveThe aims of this preliminary study were to evaluate the antioxidant and lipid status before and after star fruit juice consumption in healthy elderly subjects, and the vitamins in star fruit extracts.MethodsA preliminary designated protocol was performed in 27 elderly individuals with a mean (±SD) age of 69.5±5.3 years, by planning a 2-week control period before 4 weeks of consumption of star fruit twice daily. Oxidative stress parameters such as total antioxidant capacity, glutathione, malondialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
5
26
0
1
Order By: Relevance
“…Oxidative stress markers such as TAC, GSH, MDA, and NO were evaluated following the protocols in previous studies 30,31. After blood was taken from the anterior cubital vein of each subject and contained in a heparinized tube, 500 μL of whole blood was separated by 5, 5′-dithiobis-2-nitrobenzoic acid reagent to determine the GSH.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress markers such as TAC, GSH, MDA, and NO were evaluated following the protocols in previous studies 30,31. After blood was taken from the anterior cubital vein of each subject and contained in a heparinized tube, 500 μL of whole blood was separated by 5, 5′-dithiobis-2-nitrobenzoic acid reagent to determine the GSH.…”
Section: Methodsmentioning
confidence: 99%
“…Excess level of MDA levels has been reported when it undergoes cell damage or in several diseased conditions. Several authors are in concordance with our results (192,193,261). Rowinski et al found that oxidative stress parameters increase was age-related; nonetheless PA can decrease oxidative stress markers and induce adaptive increase in the erythrocyte antioxidant enzyme activity, mainly SOD, even in old and very old males and females (301).…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, we found that CAT Lmf was associated whit higher intake of fruits per day in females. The results obtained are in concordance with others authors (148,192,204), nevertheless, the regression model showed an inverse relationship between vitamin E intake and CAT Plm. This may be due to a considerable number of participants presented intake below EAR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations